BODY METAPHOR IN ENGLISH AND RUSSIAN LINGUOCULTURES - Yu. A. Bashkatova (Вестник Кемеровского государственного университета, 2013)
The article focuses on the identification of ethnocultural peculiarities of body metaphor functioning in differentstructure languages – English and Russian. According to cognitive theory, human reason arises from the nature of our brains, bodies, and bodily experience. Language material, however, suggests the necessity of taking into account cultural factors of body metaphor formation.